BIODEGRADASI PHENANTRENE OLEH MIKROBA LAUT M5 (ALCANIVORAX BORKUMENSIS) YANG DIISOLASI DARI TELUK JAKARTA - Supriyati, Dyah (JURNAL BIOLOGI INDONESIA, 2009)
ABSTRACTBiodiversity of Phenanthrene by Alcanivorak borkumensis M5 Isolated from Teluk Jakarta.Phenantrene is one of the most persistent organic substances in environment. AlcanivoraxBorkumensis M5 was isolated from sea water, and able to degrade phenantrene after 5 hours.About 75 % of phenantrene was degraded after 12 hours. This isolate grew optimum at 300C,pH 7.8 with a doubling time of 14.5 hours and specific growth rate of 0.0476/hour.Polyhydroxybutirate (PHB) was produced during culture growth, but the synthesis wasinversely correlated with the cell growth. The relation between PHB synthesis and phenantrenedegradation is due required further investigation.Keywords: Phenanthrene, degradation ,bacteriaKata kunci: Phenantren, degradasi, bakteri